Implementasi Metode Performance Prism Pada Berbagai Bidang: Kajian Literatur - Bambang Setiawan; Humiras Hardi Purba; hasbullah hasbullah (Journal of Industrial and Engineering System, 2021)
Performance Prism has been implemented in various business, because it is a method to measure company performance. Therefore, a systematic literature review is required, to provide information for further research about the implementation of Performance Prism. The identified literature includes 36 national articles and 4 international articles from Indonesia, with a range of publications from 2011 to 2020. The implementation of Performance Prims is dominated by the industry of food, apparel, and construction materials, as well as services of raw water and health. In addition, Performance Prism is also implemented in educational institutions, includes Junior High School and University. The implementation of Performance Prism is integrated by 4 other dominant methods, includes Analytical Hierarchy Process (AHP), Objective Matrix (OMAX), Traffic Light System (TLS), and Strengths, Weaknesses, Opportunities, & Threats (SWOT). The benefits of implementing Performance Prism consist of measuring the level of perspective stakeholders and performance indicators, as well as determining Key Performance Indicators and measuring company performance.